Octopamine-mediated circuit mechanism underlying controlled appetite for palatable food in Drosophila. - Zhang, T.; Branch, A.; Shen, P. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
The easy accessibility of energy-rich palatable food makes it difficult to resist food temptation. Drosophila larvae are surrounded by sugar-rich food most of their lives, raising the question of how these animals modulate food-seeking behaviors in tune with physiological needs. Here we describe a circuit mechanism defined by neurons expressing tdc2-Gal4 (a tyrosine decarboxylase 2 promoter-directed driver) that selectively drives a distinct foraging strategy in food-deprived larvae. Stimulation of this otherwise functionally latent circuit in tdc2-Gal4 neurons was sufficient to induce exuberant feeding of liquid food in fed animals, whereas targeted lesions in a small subset of tdc2-Gal4 neurons in the subesophageal ganglion blocked hunger-driven increases in the feeding response. Furthermore, regulation of feeding rate enhancement by tdc2-Gal4 neurons requires a novel signaling mechanism involving the VEGF2-like receptor, octopamine, and its receptor. Our findings provide fresh insight for the neurobiology and evolution of appetitive motivation.